Documented occurrence of Formicivora grisea (Boddaert, 1783) (Aves: Thamnophilidae) in spits - Guzzi, Anderson; Gomes, Deimes do Nascimento; Tavares, Antonio Alves; Cardoso, Cleiton Oliveira; Branco, Mário Sérgio Duarte; dos Santos, Antonio Gildo Soares (Comunicata Scientiae, 2015)
Formicivora grisea (Boddaert, 1783) (Aves: Thamnophilidae), popularly known as white–fringed antwren, is a common species in Brazil, occurring from the Amazon to eastern part of this country, living in the edges of wet and dry forests, secondary forest, capoeira and Restinga Forest, Caatinga Forest and secondary forest. This study presents a documented record and ringing of two individuals of this species on the coast of Piauí. The specimens, a female and a male, were captured with mist nets during sampling effort on a Restinga area with elements of Cerrado and Caatinga the aim of the avifauna characterization and inventory on the ecosystem situated near the International Airport of Parnaíba, Piauí, on 12/IX/2010..